(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2021)
Objective: To identify the benefits of ozone therapy in the treatment of foot ulcers in people with diabetes mellitus. Method: Literature review carried out in the CINAHL, Cochrane Library, LILACS, PUBMED, SciELO, SCOPUS and Web of Science databases in the period between April and May 2020. In each database, the controlled descriptors were delimited in the Science Descriptors of Health and Medical Subject Headings, keywords defined: Ozone (Ozone), Diabetic Foot (Diabetic foot), with the help of the Boolean operator AND. Results: 14 primary studies were selected. Most studies have level II evidence, published in English, in different journals, from different parts of the world. 15 benefits of ozone therapy for the treatment of foot ulcers were identified, with a predominance of increased granulation tissue and intensification in the progress of tissue repair. Conclusion: The use of ozone therapy has shown several benefits in the progress in tissue repair of foot ulcers in people with diabetes, increased granulation tissue, promoted antiseptic and bactericidal activities, preventing oxidative stress.